Evaluation of the Clinical Features of Bronchiolitis in Paediatric Patients and Exploration of the Risk Factors (Journal of Monno Medical College, 2023)
Background: In general, bronchiolitis presents as a progressive viral respiratory illness in children younger than 2 years of age, most commonly between 2-6 months.Objective: The study was conducted to assess the clinical presentations of acute bronchiolitis in infants and young children and to evaluate the individual characteristics and environmental factors which can increase the risk of severe disease and hospitalization.Methodology: This descriptive study was conducted in the department of Paediatrics, Khwaja Yunus Ali Medical College and Hospital, Enayetpur, Sirajganj. A total of 70 patients were included in the study, who were admitted to the hospital with a clinical and radiological diagnosis of acute bronchiolitis and were followed up in the Paediatric department during January, 2021 to December, 2021. Data collection was done by using a questionnaire form and by physical examination. The information for the questionnaire was provided by the childrens’ mothers. The SPSS software was used for data analysis.Results: According to the results of the study, 39(55.7%) children were infants, aged between 2-6 months, 21(30.0%) were between 7-12 months and 10(14.3%) children of more than 12 months of age. Boys (47, 67.1%) were affected more commonly than girls (23, 32.9%) in a ratio of 2:1. Some 60 (85.7%) of the children had siblings and 46 (65.7%) children lived in crowded environment at home. Many (25, 35.7%) parents of the children were cigarette smokers and 37(52.9%) children were given formula feeds. There was previous history of hospitalization among 14(20.0%) cases and 5(7.1%) children were pre-term. The most common clinical presentations of bronchiolitis were cough among 61(87.1%) cases, wheeze in 56(80.0%), respiratory distress in 49(70.0%) and feeding difficulty in 28(40.0%) children.Conclusion: The risk factors for bronchiolitis were young age (2-6 months), presence of a sibling, a history of hospital admission, crowding and paternal smoking at home and formula feeding. The most common clinical presentations were cough, wheeze and respiratory distress.J Monno Med Coll June 2022;8(2): 48-52